2013
DOI: 10.1038/ncomms2537
|View full text |Cite
|
Sign up to set email alerts
|

De novo lipogenesis in human fat and liver is linked to ChREBP-β and metabolic health

Abstract: Clinical interest in de novo lipogenesis has been sparked by recent studies in rodents demonstrating that de novo lipogenesis specifically in white adipose tissue produces the insulin-sensitizing fatty acid palmitoleate. By contrast, hepatic lipogenesis is thought to contribute to metabolic disease. How de novo lipogenesis in white adipose tissue versus liver is altered in human obesity and insulin resistance is poorly understood. Here we show that lipogenic enzymes and the glucose transporter-4 are markedly d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
234
3
5

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 263 publications
(265 citation statements)
references
References 59 publications
19
234
3
5
Order By: Relevance
“…As a result, insulin stimulates glucose uptake in the adipocytes, activates glycolytic and lipogenic enzymes, and stimulates the expression of lipogenic gene sterol regulatory element-binding protein 1 (SREBP1) that controls the expression of genes required for cholesterol, fatty acids, TG and phospholipid synthesis (Assimacopoulos-Jeannet et al 1995, Ferre & Foufelle 2007. In addition to SREBP1, another transcriptional factor carbohydrate response element-binding protein (ChREBP) promotes de novo lipogenesis (DNL) gene expression and has been shown to modulate both lipid and glucose metabolism in adipose tissue and substantial whole-body insulin sensitivity (Herman et al 2012, Eissing et al 2013). However, under normal conditions, DNL is relatively low in WAT compared with liver and BAT in rodents and even lower in humans (Swierczynski et al 2000, Letexier et al 2003.…”
Section: Adipose Tissue As An Energy Storage Organmentioning
confidence: 99%
“…As a result, insulin stimulates glucose uptake in the adipocytes, activates glycolytic and lipogenic enzymes, and stimulates the expression of lipogenic gene sterol regulatory element-binding protein 1 (SREBP1) that controls the expression of genes required for cholesterol, fatty acids, TG and phospholipid synthesis (Assimacopoulos-Jeannet et al 1995, Ferre & Foufelle 2007. In addition to SREBP1, another transcriptional factor carbohydrate response element-binding protein (ChREBP) promotes de novo lipogenesis (DNL) gene expression and has been shown to modulate both lipid and glucose metabolism in adipose tissue and substantial whole-body insulin sensitivity (Herman et al 2012, Eissing et al 2013). However, under normal conditions, DNL is relatively low in WAT compared with liver and BAT in rodents and even lower in humans (Swierczynski et al 2000, Letexier et al 2003.…”
Section: Adipose Tissue As An Energy Storage Organmentioning
confidence: 99%
“…In adolescents with impaired glucose tolerance or T2DM, the expression of Chrebp is decreased in adipose tissue but increased in the liver [75]. It has been reported that decreased expression of Chrebp causes a decrease in peripheral glucose uptake and worsens insulin resistance through decreased expression of glucose transporter type 4 (Glut4) mRNA [25,76]. The finding of a novel ChREBP isoform is significant and fascinating.…”
Section: The Physiological Role Of Chrebp In Adipose Tissuesmentioning
confidence: 82%
“…In addition, Chrebp mRNA expression decreases during the development of non-alcoholic steatohepatitis [70]. A couple of groups have reported that in adolescents with impaired glucose tolerance or T2DM (type 2 diabetes mellitus), the expression of ChREBP was increased in the liver [75,76]. Similarly, hepatic Chrebp mRNA levels in obese subjects were much higher than in lean subjects [77].…”
Section: The Physiological Role Of Chrebp In Pancreatic Isletsmentioning
confidence: 97%
“…Dans une autre cohorte de sujets obèses (BMI = 38) et insulino-résistants (classés selon trois groupes : 1-glycémie < 120 mg/dl ; 2-glycémie comprise entre 120 et 140 mg/dl ; 3-glycémie > 140 mg/dl), une corrélation positive entre l'expression de ChREBPα (mais pas de ChREBPβ) et la sévérité de la résistance à l'insuline a pu être mise en évidence [30]. L'étude de Eissing et collaborateurs [31], quant à elle, rapporte une corrélation positive entre la résistance à l'insuline et l'expression de ChREBPβ dans le foie de sujets obèses et résistants à l'insuline (BMI = 54). Au contraire, il a été rapporté que l'expression de ChREBP était corrélée de manière négative à la résistance à l'insuline dans une cohorte de patients atteints de stéatohépatite (NASH) (BMI = 31) [23].…”
Section: Chrebp Et Sensibilité à L'insuline : Une Relation Complexe ?unclassified
“…En effet, une corrélation négative entre l'expression de ChREBPβ dans le tissu adipeux sous-cutané et l'indice de résistance à l'insuline a été observée pour des individus de corpulence identique (37,4 < BMI < 38,5) dans une cohorte d'adolescents pré-diabétiques [30]. De la même façon, une corrélation inverse entre l'expression de ChREBPβ dans le tissu adipeux viscéral de patients obèses (BMI = 51,4) et la résistance à l'insuline a pu être également mise en évidence [31]. Il est important de noter que si les corré-lations sont nettes pour ChREBPβ dans ces deux études, elles le sont beaucoup moins pour ChREBPα.…”
Section: Un Rôle Insulino-protecteur Dans Le Tissu Adipeuxunclassified